Effect of Vitamin D or Activated Vitamin D on Circulating 1, 25-Dihydroxyvitamin D Concentrations: A Systematic Review and Metaanalysis of Randomized Controlled Trials. (6th January 2020) - Zittermann, Armin; Ernst, Jana B; Birschmann, Ingvild; Dittrich, Marcus
Abstract: BACKGROUND: Evidence is accumulating that circulating 1, 25-dihydroxyvitamin D [1, 25(OH)2 D] concentrations are inversely related to overall mortality. METHODS: We searched PubMed, Embase and ISI Web of Science for randomized controlled trials with a control group receiving a placebo instead of vitamin D/activated vitamin D and performed a metaanalysis to evaluate the effect of oral vitamin D/activated vitamin D on circulating 1, 25(OH)2 D concentrations using a random effects model. RESULTS: We included 52 vitamin D intervention groups (4796 individuals) and 14 intervention groups with activated vitamin D (668 individuals). Vitamin D supplements increased circulating 1, 25(OH)2 D by 12.2 pmol/L (95% CI, 7.8–16.5 pmol/L) and 18.8 pmol/L (95% CI, 9.2–28.4 pmol/L) if only studies with a low risk of bias in study design and reporting were considered (n = 18). There was significant heterogeneity among studies (Cohran's Q P < 0.001, I 2 = 91%). The incremental effect was larger in studies using vitamin D alone compared with coadministration of calcium supplements (18.6 pmol/L; 95% CI, 12.7–24.4 pmol/L vs 4.9 pmol/L; 95% CI, −0.4 to 10.2 pmol/L; P = 0.001), and if quantification was performed with RIA vs other methods (17.1 pmol/L; 95% CI, 11.1–23.1 pmol/L vs 6.9 pmol/L; 95% CI, 1.0–12.8 pmol/L; P = 0.02). Activated vitamin D increased the mean circulating 1, 25(OH)2 D by 20.5 pmol/L (95% CI, 8.3–32.7 pmol/L; P = 0.04). Again, there was evidence for significant heterogeneity among studies (Cochran Q = 85.4; P < 0.001; I 2 = 87%), but subgroup analysis did not identify parameters significantly influencing the increment in 1, 25(OH)2 D concentrations. CONCLUSIONS: Both vitamin D and activated vitamin D significantly increase circulating 1, 25(OH)2 D concentrations, but in vitamin D users this increase is suppressed by calcium coadministration.